Vaccination of dogs with Duramune DAPPi+LC protects against pathogenic canine parvovirus type 2c challenge. (22nd June 2013) - Wilson, S.; Stirling, C.; Borowski, S.; Thomas, A.; King, V.; Salt, J.
Abstract : In this study, we determined whether vaccination with Duramune DAPPi+LC containing canine parvovirus (CPV) type 2b protects against challenge with virulent CPV antigenic type 2c. Seven healthy dogs, seronegative for CPV2, were enrolled into two treatment groups; five were vaccinated twice, 21 days apart, with minimum titre vaccine, and two were given saline. Dogs were challenged with CPV 2c three weeks later. Clinical observations, body weight and rectal temperature measurements, blood samples for serology and white blood cell counts and faecal samples for virus excretion were collected. Control dogs remained seronegative until challenge; vaccinated dogs seroconverted and were positive for antibodies to CPV2 from day 21. Four days after challenge, clinical signs associated with parvovirus infection (vomiting, paroxysmal shivering, depression, loose stools) were observed in the control dogs. Both animals were withdrawn from the study for welfare reasons one day later. On day 47, leucopenia was observed in controls, with white blood cell counts less than 50 per cent prechallenge values. No specific clinical sign of parvovirus infection were observed in the vaccinated dogs, nor was (detectable) challenge virus shed in faeces suggesting that antibodies generated contributed sterilising immunity. We conclude that vaccination of dogs with Duramune DAPPi+LC protects against challenge with a virulent field strain of CPV 2c.